2019
DOI: 10.1111/bjh.16176
|View full text |Cite
|
Sign up to set email alerts
|

In situ BCL2 expression is an independent prognostic factor in HIV‐associated DLBCL, a LYMPHOVIR cohort study

Abstract: The prognostic value of cell of origin (COO) classification and BCL2 expression is not well established in diffuse large B-cell lymphoma (DLBCL) patients with human immunodeficiency virus (HIV) infection in the recent era. Phenotypic patterns were determined by immunohistochemistry (IHC) of pathological samples from patients with HIV-associated DLBCL prospectively enrolled in the French AIDS and Viral Hepatitis CO16 Lymphovir cohort between 2008 and 2015. Molecular subgroup classification into germinal centre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 77 publications
(141 reference statements)
1
9
0
Order By: Relevance
“…Herein, in line with a previous report by Chao et al ., we identified a higher frequency of non‐GC types in HIV‐associated DLBCL than that reported in immunocompetent patients 41 . Regarding the prognostic impact of COO, two previous studies on HIV‐associated DLBCL showed that the Hans algorithm could identify cases with worse outcomes 43,47 . In the present study, a larger series of HIV‐associated DLBCL treated with RCHOP we observed that non‐GC cases tended to have a worse OS and PFS than GC cases, although without statistical significance.…”
Section: Discussionsupporting
confidence: 43%
“…Herein, in line with a previous report by Chao et al ., we identified a higher frequency of non‐GC types in HIV‐associated DLBCL than that reported in immunocompetent patients 41 . Regarding the prognostic impact of COO, two previous studies on HIV‐associated DLBCL showed that the Hans algorithm could identify cases with worse outcomes 43,47 . In the present study, a larger series of HIV‐associated DLBCL treated with RCHOP we observed that non‐GC cases tended to have a worse OS and PFS than GC cases, although without statistical significance.…”
Section: Discussionsupporting
confidence: 43%
“…Previous clinical investigations of the LYMPHOVIR cohort revealed that the PFS in PLHIV with DLBCL was not different from that of their HIV-negative counterparts, and that only lymphoma-specific clinical variables predicted survival in this scenario [ 46 ]. According to the findings of [ 146 ], tumor histogenesis is an independent predictor of lymphoma-specific survival in PLHIV with DLBCL in the cART era. These findings may encourage the use of BCL2-targeted drugs in future prospective investigations of HIV-infected DLBCL patients [ 146 ].…”
Section: Viruses In Dlbclmentioning
confidence: 99%
“…According to the findings of [ 146 ], tumor histogenesis is an independent predictor of lymphoma-specific survival in PLHIV with DLBCL in the cART era. These findings may encourage the use of BCL2-targeted drugs in future prospective investigations of HIV-infected DLBCL patients [ 146 ].…”
Section: Viruses In Dlbclmentioning
confidence: 99%
“…Some studies showed that the frequency of double expressors is similar between HIV-DLBCL and immunocompetent patients ( 193 ). However, its prognostic relevance was not yet addressed in the HIV-infected context, even though cMYC ( 179 ) and BCL2 ( 194 ) expression were described separately as prognostic factors for HIV-DLBCL. Similarly, another immunohistochemistry study detected high frequency (around 40%) of HIV-DLBCL samples positive for BCL6 and MUM1 ( 180 ).…”
Section: Molecular Characteristics Of Hiv-related Dlbclmentioning
confidence: 99%